Indicador de vazão ambiental (IVA): uma proposta metodológica para avaliar impactos ecohidrológicos do uso e ocupação do solo em escala de bacia - Santos, Cledeilson Pereira (2018)
The dynamics of rivers and their ecosystems are directly related to the condition of native vegetation cover. The substitution of this by different combinations of use and occupation of the alone to meet the human needs, has been compromising the integrity of aquatic ecosystems through changes in the hydrological cycle, water quality and structure of habitats, generating losses for society with the loss of goods and services provided by these environments. With population growth at the global level, mechanisms for evaluation and monitoring of due to the anthropic pressures on the water bodies and their ecological state. Flow is a key variable for the maintenance of environmental systems. Therefore, it is in this that the concept of environmental flow emerges as a means of applying the principles of ecohydrology and as a basic requirement for the integrated management of water resources, social and economic development in the river basin and at the same time guaranteeing water quality and quantity to meet the demands of ecosystems. Before this scenario, the present work developed the Environmental Flow Indicator (IVA) and proposes as a tool to assist in the preliminary qualification of the ecological status of bodies in order to identify critical points that need for the maintenance of quantitative and qualitative aspects of water. Applied in the basin the Quixeramobim River (Ceará State) with fictitious scenarios, VAT was coupled with to the SWAT hydrological model and presented satisfactory results not only for the estimation of water bodies, but also to measure the progress of programs for the sustainable management of water resources and as a tool for qualitative and quantitative monitoring of water in locations where there is a lack of data.